Korelasi Stenosis Penyakit Arteri Perifer di Bawah Lutut dengan Kecepatan Hantar Saraf pada Penyandang Neuropati Perifer Diabetes Melitus Tipe 2 - Antono, Akbarbudhi; Antono, Dono; Karim, Birry; Hakim, Manfaluthy; Harimurti, Kuntjoro; Sulistianingsih, Dyah Purnamasari; Ginanjar, Eka; Nelwan, Erni Juwita; Nugroho, Pringgodigdo (UI Scholars Hub, 2025)
Introduction. One consequence of DM is the emergence of peripheral artery disease (PAD) and diabetic peripheral neuropathy (DPN). Diabetic peripheral neuropathy is a complication of diabetes that presents signs and symptoms of motor and sensory disturbances, while PAD is an atherosclerosis condition that gradually develops in the arterial vessels. This study aimed to determine correlation of arterial obstruction assessed using arteriography and the nerve impairment assessed using nerve conduction velocity (NCV) in DM patients with PAD and DPN. Methods. This is a cross-sectional study that takes secondary data from previous research conducted from July 2018 to June 2021 in Cipto Mangunkusumo hospital. Subjects were people with DM type 2 who had NPD and PAP who met the inclusion criteria and did not meet the exclusion criteria. Subjects underwent an arteriography examination to assess the stenosis in the peroneal artery, anterior tibial artery, and posterior tibial artery. Subjects also underwent nerve conduction velocity (NCV) examinations in the peroneal N. communis, N. peroneal superficialis, N. tibialis, and N. suralis. The correlation between the two variables was then tested using the Spearman correlation test. Results. The peroneal artery stenosis had a moderate negative correlation (r = - 0.420) with the sensory NCV of the superficial peroneal nerve which was statistically significant (p = 0.023). Meanwhile, the correlation of stenosis and NCV disorders in the peroneal nerve with the common peroneal nerve, anterior tibial nerve with tibialis nerve and posterior tibial nerve with sural nerve was not statistically significant. This can be explained by the possibility of collaterals appearing in people with PAD, the structure of vasculature on the nerves, and the small number of samples. Conclusions. There is a moderate negative correlation between the stenosis of the peroneal nerve and the sensory NCV of the peroneal superficialis. However, insignificant results were found in the correlation between peroneal artery with common peroneal nerve, anterior tibialis artery with tibial nerve, and posterior tibial artery with sural nerve.